Museum für Neue Kunst - ZKM Karlsruhe. : Museumsführer. - Adriani, Götz; Jürgens, Christiane; Melcher, Ralph; Meyer-Büser, Susanne; Schalhorn, Andreas; Sölch, Brigitte; ZKM, Zentrum für Kunst und Medientechnologie, Karlsruhe (München : Prestel Verlag, 2002)
Albers, Josef ; Andre, Carl ; Baselitz, Georg ; Basquiat, Jean-Michel ; Beuys, Joseph ; Bonin, Cosima von ; Riverhead (New York) ; Fleury, Sylvie ; Förg, Gunther ; Gillick, Liam ; Haring, Keith ; Herold, Georg ; Judd, Donald ; Kawara, On ; Kelly, Ellsworth ; Kiecol, Hubert ; Kiefer, Anselm ; Kippenberger, Martin ; Klein, Yves ; Knoebel, Imi ; Kosuth, Joseph ; Kounellis, Jannis ; LeWitt, Sol ; Lichtenstein, Roy ; Louis, Morris ; Martin, Agnes ; Merz, Mario ; Mucha, Reinhard ; Drescher, Jürgen ; Nauman, Bruce ; Noland, Kenneth ; Oehlen, Albert ; Paolini, Giulio ; Penone, Giuseppe ; Polke, Sigmar ; Rauschenberg, Robert ; Rehberger, Tobias ; Richter, Gerhard ; Rothko, Mark ; Stella, Frank ; Trockel, Rosemarie ; Twombly, Cy ; Warhol, Andy ; Wesselmann, Tom ; West, Franz ; Zobernig, Heimo
Duits
boek